Fear of missing out (FoMO) and internet addiction among adolescence: The moderation effect of gender differences - Martaria Rizky Rinaldi (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
The use of the internet and its impact on adolescents is an increasingly important topic in the current digital era. This study explores the moderating role of gender in the relationship between Fear of Missing Out (FoMO) and internet addiction among adolescents in Indonesia. Data were collected through an online survey involving 169 participants. The scales used were the Internet Addiction Scale and the FoMO Scale. Statistical analysis employed moderation analysis using Jamovi. The results showed that FoMO significantly influences internet addiction, and there are gender differences in the level of internet addiction. However, the study also found that gender did not significantly moderate the relationship between FoMO and internet addiction. This implies that FoMO and gender independently contribute to internet addiction, emphasizing their distinctive roles in shaping online behaviors. The study underscores the importance of considering both factors in designing effective prevention and intervention strategies.